Economic Feasibility of Trawling Operations Off Tuticorin Coast - R., Senthilathiban; P., Selvaraj; R.K., Ramkumar (Fishery Technology, 2025)
The economic feasibility of medium size trawlers of 36 feet length operating at Tuticorin coast was studied. The size of sample fishermen respondents was fixed at 30. Data collection was carried out once in a fortnight and thus a total of 60 fishing trips were considered in a month. Data on auction revenue, cost of operation and total fish catch were collected for one year from July 1997 to June 1998. The economic estimates were made for an average fishing trip. The key economic indicators which would indicate the economic feasibility of trawling operations were estimated.